An automated chemiluminescent immunoassay (CLIA) detects SARS-CoV-2 neutralizing antibody levels in COVID-19 patients and vaccinees. (February 2022) - Liu, Binjian; Su, Xibin; Yu, George; Yang, Shuling; Wang, Feng; Huang, Tao; Zhou, Liuyong; Hui, Zhiqiang; Liao, Yixian; Qiu, Yuan; Huang, Juan; Gao, Hong; et al.
Highlights: Chemiluminescent immunoassay can replace microneutralization test for testing severe acute respiratory syndrome coronavirus-2 neutralizing antibodies. Mathematical models can evaluate the effectiveness, protectiveness and durability of vaccines. Only 5.35% of vaccinees had protective capability of NAb following the second dose of vaccine. People should receive a third dose of vaccine, and the vaccine should be administered once every 6 months. ABSTRACT: Objectives: A specific and sensitive automated chemiluminescent immunoassay (CLIA) was developed to detect neutralizing antibody (NAb) levels. This assay can be used for the diagnosis of severe acute respiratory syndrome coronavirus-2 (SARS-CoV-2) infection, treatment and vaccine evaluation. Methods: The SARS-CoV-2 receptor-binding domain (RBD) and a stabilized version of the spike ectodomain as antigens were detected by CLIA. Sera NAb titers and concentrations from 860 SARS-CoV-2 vaccinees, 232 SARS-CoV-2 convalescent patients and 675 healthy individuals were tested by microneutralization test (MNT) and CLIA, respectively. Mathematical models were established to evaluate the relationship between two variables in different groups. Conclusions: With the RBD-based CLIA protocol, CLIA can be used to replace MNT to test SARS-CoV-2 NAb. Vaccine effectiveness, protectiveness and durability can be evaluated effectively by mathematical models. It is Results: Analysing the relationship between NAb titers and concentrations, R 2 for the decision-making tree was 0.870 and that of progressive linear fitting was 0.821. The receiver operating characteristic curve indicated specificity of 78.1%, sensitivity of 87.4%, cut-off value of 6.43 AU/mL and borderline range of 5.79–7.07 AU/mL for CLIA. Three-quarters (75.4%) of vaccinees were found to be NAb positive, and 5.35% vaccinees had NAb protective capability. The half-life of NAb in vaccinees was 10–11 weeks.for vaccinees to take a NAb assay periodically. Graphical abstract: Image, graphical abstract